2006
DOI: 10.1154/1.2358363
|View full text |Cite
|
Sign up to set email alerts
|

Powder X-ray diffraction and Rietveld analysis of La1−xBaxCoO3 (0<x≤0.5)

Abstract: Detailed structural properties of La 1−x Ba x CoO 3 ͑LBCO͒ have been investigated by means of X-ray powder diffraction and Rietveld analysis. A structural phase transformation from R3c to Pm3m at x = 0.30-0.35 has been detected based on a comparison between the refinements of R3c and Pm3m. The Co-O bond length of the CoO 6 octahedron expanded rapidly with increasing Ba content when x Ͻ 0.1, and then it leveled off and kept constant at 0.1ഛ x ജ 0.35, where the Co-O-Co bond angle reaches 180°. The Co-O bond leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 11 publications
6
12
0
Order By: Relevance
“…26 As the Ba content increases, the rhombohedral distortion fades out, and the symmetry of the crystal structure becomes cubic (SG Pm3m) 11 for samples with x = 0.5−0.7. This result is in close agreement with the work of W. Lou et al, 26 who reported the transition from the rombohedral to the cubic symmetry at x ∼ 0.3−0.35. On the other hand, the x = 1.0 sample was refined based on the crystallographic data of the 12H hexagonal phase (SG P 63/mmc) reported by Jacobson and Hutchinson for BaCoO 2.6 .…”
Section: Methodsmentioning
confidence: 99%
“…26 As the Ba content increases, the rhombohedral distortion fades out, and the symmetry of the crystal structure becomes cubic (SG Pm3m) 11 for samples with x = 0.5−0.7. This result is in close agreement with the work of W. Lou et al, 26 who reported the transition from the rombohedral to the cubic symmetry at x ∼ 0.3−0.35. On the other hand, the x = 1.0 sample was refined based on the crystallographic data of the 12H hexagonal phase (SG P 63/mmc) reported by Jacobson and Hutchinson for BaCoO 2.6 .…”
Section: Methodsmentioning
confidence: 99%
“…Polycrystalline samples of La 1Àx Ba x CoO 3 (LBCO) in the range of 0.0oxo0.18 were fabricated from La 2 O 3 , BaCO 3 and Co 3 O 4 starting materials by the standard solid-state reaction method and X-ray powder diffraction confirmed that the samples were in high purity [25]. dc Magnetization as a function of temperature and external magnetic field was derived using a SQUID magnetometer (Quantum Design MPMS-7).…”
Section: Methodsmentioning
confidence: 99%
“…In this group of materials the metal‐insulator transition was observed, as well as high ionic conductivity . Additionally, the spin configuration of cobalt may vary for this system causing the antiferromagnetic, ferromagnetic and even spin glass behavior . Moreover, high‐temperature electrical properties Ba 0.5 La 0.5 CoO 3 (BLC) have been intensively studied for their potential application as electrode material for intermediate temperature solid oxide fuel cells and electrolyzers (IT‐SOFC/ ‐SOEC) …”
Section: Introductionmentioning
confidence: 99%
“…Lanthanum barium cobaltites crystallize in two crystal structures, that is, disordered cubic (Ba 1− x La x CoO 3− δ ), and ordered tetragonal (BaLaCo 2 O 6 ) . In the cubic phase, La and Ba cations occupy the same perovskite A‐site, while in the tetragonal polymorph, divalent barium and trivalent lanthanum cations form alternating layers of [Co‐O]/[Ba‐O]/[Co‐O]/[La‐O] along the c ‐axis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation